USING ADAPTIVE CONTROL ALGORITHMS IN WATER TREATMENT SYSTEMS (Municipal economy of cities (Technical science), 2013)
Formulate the problem of water treatment systems management. The possibility of using adaptive control algorithms for optimization of water treatment facilities.